2022
DOI: 10.3390/en15238982
|View full text |Cite
|
Sign up to set email alerts
|

Power Plant Cycles: Evolution towards More Sustainable and Environmentally Friendly Technologies

Abstract: The scarcity of energy and water resources and rising temperatures due to climate change has set the focus on improving the energy efficiency of power plant thermodynamic cycles to adapt to higher heat sink temperatures and use fewer resources for energy production. In this work, a review of power production thermodynamic cycles is presented: from Brayton to Rankine and combined cycles, alongside particular cycles such as Organic Rankine Cycles, Kalina, Goswami or the more recently developed Hygroscopic Cycle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 94 publications
1
7
0
Order By: Relevance
“…The energy efficiencies of the equipment were calculated as 35.34% for the evaporator, 98% for the turbine, 54.66% for the condenser and 70.44% for the pump. This energy efficiency value is within the range of the values provided in [13], and the exergy efficiency value is in concordance with the values provided in [39]. When we look at the evaporator and condenser in the plant, it is seen that they have lower energy efficiency than the other equipment.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…The energy efficiencies of the equipment were calculated as 35.34% for the evaporator, 98% for the turbine, 54.66% for the condenser and 70.44% for the pump. This energy efficiency value is within the range of the values provided in [13], and the exergy efficiency value is in concordance with the values provided in [39]. When we look at the evaporator and condenser in the plant, it is seen that they have lower energy efficiency than the other equipment.…”
Section: Resultssupporting
confidence: 88%
“…If not properly managed, it is released into the environment, contributing to global warming. The literature research has identified several areas of use for waste heat, including district heating systems [2,3,67], greenhouses [4], industrial processes and process heating [3], thermal energy storage [5,6], seawater desalination [7][8][9][10], cooling systems and cold storage [10], agriculture and aquaculture [3], direct conversion of thermal energy into electrical current [11], and generating electricity (ORC) [12,13]. This text will discuss recent studies on some important issues related to these areas.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations